The Common Flaw : Needless Complexity in the Courts and 50 Ways to Reduce It - Moukawsher, Thomas G., 1962- (Book collections on Project MUSE., 2023)
"The American lawsuit is riddled with needless complexity. This book proposes fifty changes-that decide cases promptly-more on the facts than the law-more for the parties than the lawyers-more for the consequences to the people and the public-and in words we can all understand"--